SKENARIO MODEL PEMILIHAN MODA KERETA API DAN MOBIL PENUMPANG RUTE PALANGKA RAYA – BANJARMASIN (Models Scenario Of Model Selection Of Railways And Passenger Cars, Training Routes – Banjarmasin) - Miming Virganinda; Linda Baktiani (Fakultas Teknik Universitas Kristen Palangka Raya, 2021)
: The government of the Regional Development Planning Agency in Palangka Raya City is planning the construction of a railway system that connects the city of Palangka Raya with Banjarmasin along 138 km. With this planning, this study specifically aims to determine what factors might later influence travelers in determining the type of mode and to find out the mode choice opportunities between trains and passenger cars. The research method starts from the literature review stage, the selected variables, data collection, variable identification, and modeling. The type of survey conducted is the Stated preference method. Based on the results of the study, it was found that the variables that significantly influence the community in choosing the mode of transportation between trains and passenger cars are the type of student work, lifestyle, income and train time. From some of these variables, it can be suggested that the opportunity to use trains will increase if the Government in this case pays attention to the travel time of trains. Keywords: Stated Preference, Mode choice, model, train